Comparison of the improved X Farmer's system of growing cowpea - Holanda, José Símplicio de; Neto, Francisco Bezerra; Filho, José Torres; Torres, Jorge Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Field experiments of cowpea Vigna unguiculata (L.) Walp. were carried out at Serra do Mel, RN, Brazil, studying isolated factors for three agricultural years, defining more productive cultivars, appropriate spacing, methods of insect control and the viability of cattle manure. Intending to verify the performance of these factors, utilizing their best previous results, and to compare them with the cropping system used by farmers, a demonstration unit of the results was set up, with plots of 0.25 ha. The systems compared were: 1. system used by farmer, Feijão -Vermelho cultivar, spacing of 1.10 m x 1.10 m with three or four plants/hill, without insect control; 2. improved system, Lisão cultivar, spacing of 1 m x 0.50 m with two plants/hill and insect control; 3. the improved system plus fertilization with 12 t/ha of cattle manure. The additional costs for the improved system in relation to the farmer's system were accounted for. System 2 showed a 32% greater yield than system 1; but the relative profit just covered the additional costs, for price rates in the harvest time. The system which showed the best performance was system 3 with a yield of 944 kg/ha. This system showed a 183% greater yield than system 1, with a higher return rate than Cr$ 2.00 per cruzeiro invested, in three price ratios used.